Probiotic peptidoglycan skeleton enhances vaccine efficacy against MRSA by inducing trained immunity via the TLR2/JAK-STAT3 pathway - Niu, Lingdi; Duan, Haoyuan; Wang, Jiaqing; Jia, Zheng; Li, Hai; Guo, Junjie; Zhang, Shuhe; Liu, Ning; Miao, Yaxin; Ge, Junwei; Wang, Fang (Frontiers in Immunology, 2025)
Trained immunity refers to the ability of trained innate immune cells to generate an immune memory that produces rapid, broad-spectrum, and long-lasting protection against heterologous stimuli. Based on the rapid and broad-spectrum protection that the peptidoglycan backbone from lactic acid bacteria, bacterium-like particles (BLPs), offers, we hypothesized that BLPs enhance protection through trained immunity. Here, we found that combining BLP with a vaccine significantly improves protective efficacy against methicillin-resistant Staphylococcus aureus (MRSA) infection, accompanied by changes in trained immunity markers. We demonstrate that BLP-induced trained immunity macrophages exhibit increased cytokine secretion and phagocytic activity in vitro. In an in vivo model, BLP confers protection against S. aureus 26003 even without specific antigens. In an ex vivo model, BLP induces increased markers of trained immunity. Transcriptome analysis suggests that BLP may induce trained immunity by activating the IL-6-JAK-STAT3 pathway through TLR2 receptor activation, thereby modulating macrophage metabolic reprogramming and function. In summary, our study establishes that BLP induction of trained immunity, along with regulated metabolic reprogramming and macrophage function, may contribute to enhancing vaccine efficacy. Our findings elucidate a novel mechanism for BLP-mediated immune enhancement, critical for the application of BLP as a vaccine vector to construct a vaccine that combines specific immune response with innate immune response.